Traceability of Pediatric Antibiotic Purchasing Pathways in Italy: A Nationwide Real-World Drug Utilization Analysis - Sultana, Janet; Trifirò, Gianluca; Ientile, Valentina; Fontana, Andrea; Rossi, Francesco; Capuano, Annalisa; Ferrajolo, Carmen (Frontiers in Pharmacology, 2020)
Purpose: The aim of the present study was to describe the purchasing patterns of a set of antibiotics used exclusively in an out-patient paediatric setting in Italy using the Farma360 wholesale drug database (IQVIA Solutions Italy), identifying the proportion of medications which are not captured by Italian NHS pharmacy claims databases and examining the implications of such findings from a public health and pharmaceutical policy perspective. Methods: Using a systematic approach, sixty-six antibiotic paediatric formulations were selected for the 5 most commonly used antibiotics in Italy in children and adolescents: amoxicillin in combination with clavulanic acid, amoxicillin, azithromycin, clarithromycin and cefixime. The Farma360 wholesale drug purchasing data was used to identify the yearly proportion of antibiotics not purchased based on National Health Service (NHS) reimbursement in primary care from 2015-2017 at the national level. The relationship between product cost and purchase outside the NHS was assessed by a scatterplot. All analyses were stratified by geographic area: Northwest, Northeast, Central and Southern Italy. Results: The proportion of antibiotics not reimbursed by the NHS increased nationally from 24% in 2015 to 29% in 2017. The antibiotic with the highest proportion of purchases outside the NHS was amoxicillin, with almost two-thirds of all amoxicillin purchases in Southern Italy being made in this way in 2017. The relationship between antibiotic price and antibiotic purchase outside the NHS was almost linear for almost all the geographic areas. Conclusions: This study showed that a large proportion of antibiotics with a paediatric formulation is purchased outside the NHS drug purchasing pathway, especially in Southern Italy, indicating that it is not possible to fully monitor drug utilisation, including appropriateness, for these antibiotics. A better strategy is needed to improve drug utilisation monitoring, such as better data collection or data linkage.